The lived experiences of pregnancy planning after breast cancer in women of childbearing age: A phenomenological study - Jeonghee Ahn; Jeehee Han (Elsevier, 2023)
Objective: This phenomenological study aimed to explore the lived experiences of planning for pregnancy after breast cancer in women of childbearing age. Methods: The study comprised 15 women with breast cancer who were considering pregnancy and childbirth. Individual in-depth interviews were conducted between November 2022 and March 2023, and the verbatim transcripts were analyzed using Colaizzi's phenomenological method. Results: Four theme clusters emerged: (1) deepening desires amidst hardships, (2) endless worries about an uncertain future, (3) unveiling the meaning of having a child, and (4) perpetual deliberations regarding unresolved dilemmas. Over time, the participants' longing for children intensified, despite the contradiction of their reduced fertility. They expressed concerns about the potential risks and challenges of pregnancy in breast cancer patients, but they attributed value to having a child as a means to restoring their health, reclaiming their ordinary lives, and providing motivation for a healthier future. The participants found making decisions regarding pregnancy to be difficult and were often influenced by others. Conclusions: This study underscores the unique challenges faced by women with breast cancer who are making fertility-related decisions. The findings contribute to a better understanding of these challenges and offer valuable insights for the development of decision aids that support shared decision-making for pregnancy after breast cancer.